Ensuring the involvement of children in the evaluation of new tuberculosis treatment regimens. - Burman, W; Cotton, M; Gibb, D; Walker, A; Vernon, A; Donald, P (Public Library of Science, 2008)
We are on the threshold of revolutionary improvements in the treatment of tuberculosis. Within five to ten years, it is likely that highly effective three-month regimens will be available to treat both active and latent drug-susceptible tuberculosis. New drug classes that have the potential to dramatically improve the treatment of multidrug-resistant tuberculosis are entering clinical trials. Children have the same right as adults to benefit from research with these new treatments. By making a deliberate choice to avoid the path of least resistance, we can ensure that both adults and children benefit from these advances in tuberculosis treatment.